Roles of Community Nurse and Environmental Management for the Elderly’s Health - Intolo, Sakorn; Klungklang, Ratdawan; Phinyo, Piyanuch (Princess of Naradhiwas University Journal, 2022)
Thailand today steps towards aged society as well as moving towards digital economy and digital society. Individuals with a risk in disease and patients with chronic disease will increase due to a rising number of aging populations. The elderly living alone in community must change their living styles due to health problem. They have to be more self-reliant. Thus, environmental management for older persons to facilitate personal self-care is a challenge for community nurses as they need to take the roles as health care provider, health educator, advocator, counselor, coordinator and collaborator at the same time. The study of the roles of community nurses will be helpful for designing surroundings to support the elderly which is a preparation for aged society in the near future.